Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150044
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Skeletal Muscle Contraction by Myosin Phosphorylation

Abstract: The striated muscle sarcomere is a highly organized and complex enzymatic and structural organelle. Evolutionary pressures have played a vital role in determining the structure-function relationship of each protein within the sarcomere. A key part of this multimeric assembly is the light chain-binding domain (LCBD) of the myosin II motor molecule. This elongated "beam" functions as a biological lever, amplifying small interdomain movements within the myosin head into piconewton forces and nanometer displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 397 publications
1
68
0
3
Order By: Relevance
“…The effects of phosphorylation of RLC MYL2 at Ser15 by the cardiac and skeletal myosin light chain kinases (MLCK) have been extensively examined (89, 126, 624). Accordingly, it was demonstrated that it renders the lever arm of MyHC stiffer, potentiates isometric and concentric force production, and increases myofilament Ca 2+ sensitivity in both cardiac and skeletal muscles, reviewed in (514, 573, 574, 618). Consistent with these findings, constitutive expression of phosphomimetic Myl2 (i.e., Ser15Asp) in myocardia prevented the development of HCM in transgenic mice carrying the HCM-linked Asp166Val MYL2 missense mutation (620).…”
Section: Myosinmentioning
confidence: 99%
“…The effects of phosphorylation of RLC MYL2 at Ser15 by the cardiac and skeletal myosin light chain kinases (MLCK) have been extensively examined (89, 126, 624). Accordingly, it was demonstrated that it renders the lever arm of MyHC stiffer, potentiates isometric and concentric force production, and increases myofilament Ca 2+ sensitivity in both cardiac and skeletal muscles, reviewed in (514, 573, 574, 618). Consistent with these findings, constitutive expression of phosphomimetic Myl2 (i.e., Ser15Asp) in myocardia prevented the development of HCM in transgenic mice carrying the HCM-linked Asp166Val MYL2 missense mutation (620).…”
Section: Myosinmentioning
confidence: 99%
“…The magnitude and time history of the enhancement depends on whether performance is assessed in electrically evoked or voluntary contractions. Enhancements of electrically evoked contractions are typically large (>20%) increases in twitch torque during the first minute after the CA and decline rapidly (Tillin and Bishop 2009;Vandenboom 2016). In contrast, enhancements of voluntary contractions are typically small (<5%) effects observable after a significant rest period, peaking 7-10 minutes after the CA (Maloney et al 2014;Tillin and Bishop 2009;Wilson et al 2013), a time when there is effectively no remaining enhancement of electrically evoked contractions.…”
mentioning
confidence: 99%
“…In muscle cells, Ca 2+ -sensitive regulatory mechanisms for the actomyosin-dependent generation of motive force have been extensively investigated, and a number of actin-linked and myosin-linked components responsible for the Ca 2+ sensitivity have been identified [11,12]. Moreover, it is well documented that Ca 2+ fluxes across the plasma membrane (PM) and the sarcoplasmic reticulum membrane of those motile cells function to control the cytoplasmic concentration of Ca 2+ and excitation-contraction coupling [13].…”
Section: Introductionmentioning
confidence: 99%